The Flourishing Language Learner: A Systematic Review of Positive Psychology and Motivation in English Language Learning - Sahril Nur; Auliyanti Sahril Nurfadhilah (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2025)
The field of second language acquisition has witnessed a